Strategi Pemasaran Usaha di Era Digitalisasi Menurut Syariat Islam - Silvia Amanda; Faridudin Malikur Rahmat (Neolectura, 2022)
This study aims to identify and analyze strategies for improving the MSME economy during the new normal period due to the impact of the Covid-19 pandemic. The objects in this study are MSME actors who use business marketing strategies. The research method used is descriptive qualitative method. The results obtained from this research show that it is necessary to take quick, precise and real steps from the government or business actors to overcome the losses that have occurred due to the pandemic and to carry out updates and evaluations over the business cycle to explore the conditions that are currently in place so that businesses can continue to survive and grow.